Pembentukan Karakter Religius Siswa di Madrasah - Wahid Khoirul Anam (DIMAR: Jurnal Pendidikan Islam, 2019)
The focus of this research problemisHow Impact formation of the religious character of the daily behavior of students in Madrasah. Objectives to be achieved in this study areto identify, analyze and describeThe formation of the religious character of the program and impact the establishment of a religious character to the everyday behavior of students in Madrasah. This study is a qualitative research The data collection method used is the method of observation, interviews and documentation respondents involved, headmaster, teachers, staff and students. Hasi these studies show that Madrasah using five methodsin order to form the religious character of students, namely:exemplary, planting discipline, habituation, and the atmosphere is conducive. These five methods are applied in routine activities such asDuha prayer, midday prayer in congregationand Habituation Tadarus Qur'an.